Optoelectronics - Uiga, Endel (New Jersey : Prentice-Hall, 1995)
Written by a design engineer with many years of practical experience, this text takes a simple, non-mathematical approach to the full spectrum of optoelectronics - from radiometry and photometry to the latest in fiber optics
1. Radiometry and Photometry. 2. Elements of Geometric Optics. 3. Radiation Sources. 4. Lasers. 5. Displays. 6. Radiation Detectors. 7. Optical Sensors and Octocouplers. 8. Principles of Fiber Optics. Index.
Includes bibliographical references.
Keywords: OPTOELECTRONICS